Current Updates of Connection Between Food Allergies and Atopic Dermatitis : a Literature Review - Muhammad Farrell Rikhad; Rendy Wijaya (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2026)
Introduction: The relationship between food allergy (FA) and atopic dermatitis (AD) involves a complex, bidirectional interplay often associated with the "atopic march." This review aims to analyze the pathological mechanisms connecting these conditions, evaluate diagnostic accuracy, and determine appropriate management and prevention strategies. Method: A comprehensive literature review was conducted using electronic databases including PubMed, MEDLINE, and Google Scholar. A total of 54 references, comprising international journals and guidelines published up to 2025, were selected based on keywords such as "atopic dermatitis," "food allergy," "sensitization," and "elimination diet." Discussion: The review highlights that AD-associated skin barrier defects, such as filaggrin mutations, facilitate epicutaneous sensitization, making AD a major risk factor for developing IgE-mediated FA. Conversely, FA can exacerbate AD symptoms, particularly in infants with moderate-to-severe disease. Diagnosis requires confirming clinical history with Skin Prick Tests, specific IgE levels, and the gold-standard Oral Food Challenge. Regarding management, while targeted elimination diets improve symptoms in confirmed cases, unnecessary dietary restrictions may lead to nutritional deficiencies and a loss of immune tolerance. Preventive strategies focusing on skin barrier restoration via daily emollient therapy show promise in reducing sensitization risks. Conclusion: A reciprocal causal relationship exists between AD and FA. AD serves as a primary route for allergic sensitization, while FA can aggravate skin inflammation. Effective management necessitates rigorous diagnostic confirmation before implementing elimination diets and prioritizes early skin barrier maintenance to potentially disrupt the progression of atopic diseases.